The Effect of Ferric Carboxymaltose on Fibroblast Growth Factor 23 (FGF23) in Children with Iron Deficiency Anemia Due to Gastrointestinal Diseases - Maria Ntoumpara; Elpis Mantadakis; Lemonia Skoura; Paraskevi Panagopoulou; Elpida Emmanouilidou-Fotoulaki; Eleftheria Parasidou; Paraskevoula Koutra; Maria Fotoulaki (Hemato)
Background: Hypophosphatemia is a known side-effect of parenteral iron administration, especially after intravenous ferric carboxymaltose (FCM). Fibroblast growth factor 23 (FGF23) is thought to play an important role in the pathophysiology of serum phosphate homeostasis. This study aimed to investigate the effects of FCM on FGF23 serum levels in FCM-treated pediatric patients with iron deficiency (ID)/iron deficiency anemia (IDA) caused by gastrointestinal diseases. Methods: Over 30 months, FGF23 serum levels were assessed prospectively in children with ID/IDA due to gastrointestinal diseases and treated with FCM infusion. Serum levels of intact FGF23 (iFGF23) were assessed and correlated to phosphate serum levels and factors of bone metabolism. Blood sampling was performed in three phases: before FCM infusion, 7–10 days after FCM infusion, and 6–8 weeks after FCM infusion. Results: A total of 42 FCM infusions were given to 35 children (20 girls) with a mean age (±SD) of 12.2 (±4.03) years (range: 2–16 years). The median levels of iFGF23 did not show a significant difference across the three phases (p = 0.56). No significant correlation was found between iFGF23 levels and 25-hydroxyvitamin D/parathyroid hormone/serum phosphate/serum calcium/alkaline phosphatase. No significant change was noted between pre- and post-treatment serum phosphate levels. However, four children (11.42%) developed asymptomatic and transient hypophosphatemia. Conclusions: No significant difference was found between pre-and post-FCM infusion serum iFGF23 levels and bone metabolism parameters. An increase of iFGF23 serum levels 7–10 days after FCM infusion was noted in patients with hypophosphatemia.